أثر الأسعار على درجة حساسية المستهلك (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2019)
يحتل موضوع الأسعار أهمية كبرى في المزيج التسويقي، فهو يُعد من حيث تخطيطه وتنفيذه وتعديله من القرارات الأكثر تأثيراً على بقية عناصر المزيج التسويقي، بالإضافة إلى تأثيرها على مبيعات المنظمة من خلال قدرته على جذب المستهلكين، لذلك فإن الأسعار تُوجّه إلى المستهلك النهائي وهو المعني بها، وعليه فإنّ هذا البحث يهدف إلى توضيح إدراك المستهلك للسعر ومدى الاستجابة له، وكذلك العوامل المؤثرة في حساسية المستهلك للسعر، بالإضافة إلى الدراسة الميدانية في الشركات الخاصة للصناعات الكيميائية التي يتضح من خلالها مدى تأثّر المستهلك بالسعر، وقد انتهى هذا البحث إلى عدد من النتائج التي تم على أساسها وضع المقترحات التي يراها الباحث مناسبة لتحقيق الهدف المنشود من هذا البحث، وأهم هذه النتائج هي الدور الهام الذي تلعبه سياسات التسعير في حساسية المستهلك تجاه أسعار منتجات الشركات الخاصة للصناعات الكيميائية، إضافة إلى العلاقة الهامة بين العوامل المؤثرة في درجة حساسية المستهلك للسعر وبين أسعار منتجات هذه الشركات.   According to the marketing mixture, the most important subject is that of prices; because of its planning, execution, and modification, it is one of the most influential decisions on the rest of marketing mixture. In addition to their impact on organized sales through their capacity to attract consumers, prices will be geared for the final consumer, being the intended target. The primary objective of this paper is to clearly explain the consumer's awareness of the price and of the extent response to it, let alone the factors affecting consumer sensitivity to prices. In addition to the field study in private companies of chemical industries which demonstrates how affected the consumer is by the price. This paper has arrived at a number of results  upon which a number of suggestions have been put forward,  which the researcher find  appropriate for achieving the intended goal of this paper. The most important of these results is the main role which the policies of price fixation can play in bringing about consumer sensitivity to the product prices of the private companies of chemical industries, and the important relation between the factors affecting the degree of consumer sensitivity to the price and the product prices of these companies.